Governing locally for sustainability: public and private organizations’ perspective in surf tourism at Aljezur, Costa Vicentina, Portugal - Machado, V.; Carrasco, P.; Contreiras, J.; Duarte, A. P.; Gouveia, D. (Tourism Planning and Development, 2018)
This study explores how a rural municipality of low population density and strong tourism intensity for the practice of recreational activities can exert a sustainable collective action in the policies and strategies of planning and development of local tourism. The study focuses on the case study of the municipality of Aljezur, in Portugal, and is applied to a dominant tourism-recreational activity, surfing. Based on a survey of relevant stakeholders, namely private and public organizations, it was possible to obtain indicators of local environmental, economic and social convergence. These allowed elaborating a proposal for a municipal sustainable management charter of the surfing tourism in the region. The conception of this charter and the consequent strategies moves the management of local tourism destinations to higher levels of institutional sustainability.